Multiple Arkadia/RNF111 Structures Coordinate Its Polycomb Body Association and Transcriptional Control - Sun, Huaiyu (American Society for Microbiology, 2014)
The RING domain protein Arkadia/RNF111 is a ubiquitin ligase in the transforming growth factor β (TGFβ) pathway. We previously identified Arkadia as a small ubiquitin-like modifier (SUMO)-binding protein with clustered SUMO-interacting motifs (SIMs) that together form a SUMO-binding domain (SBD). However, precisely how SUMO interaction contributes to the function of Arkadia was not resolved. Through analytical molecular and cell biology, we found that the SIMs share redundant function with Arkadia's M domain, a region distinguishing Arkadia from its paralogs ARKL1/ARKL2 and the prototypical SUMO-targeted ubiquitin ligase (STUbL) RNF4. The SIMs and M domain together promote both Arkadia's colocalization with CBX4/Pc2, a component of Polycomb bodies, and the activation of a TGFβ pathway transcription reporter. Transcriptome profiling through RNA sequencing showed that Arkadia can both promote and inhibit gene expression, indicating that Arkadia's activity in transcriptional control may depend on the epigenetic context, defined by Polycomb repressive complexes and DNA methylation.